2008
DOI: 10.1375/acri.41.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Women's Pathways to Jail: Analysing the Lives of Incarcerated Women

Abstract: S ome researchers suggest that crime pathways are gendered and that different paths may be revealed depending on the point of contact with the criminal justice system. Drawing from the feminist and age-of-onset literatures, we examine the life experiences of a sample of 'high-risk' women to assess whether their offending pathways into jail are consistent with those predicted by earlier research. We find substantial overlaps with feminist pathways, but notable differences as well -differences that may lie with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
129
1
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(153 citation statements)
references
References 33 publications
16
129
1
7
Order By: Relevance
“…This mostly African American sample tended to have a fairly stable lifestyle, but they did have more exposure to violent victimization such as rape, robbery, and assault by partners and non-partners than the other onset groups [49].…”
Section: Accounting For Different Onset Patternsmentioning
confidence: 82%
See 1 more Smart Citation
“…This mostly African American sample tended to have a fairly stable lifestyle, but they did have more exposure to violent victimization such as rape, robbery, and assault by partners and non-partners than the other onset groups [49].…”
Section: Accounting For Different Onset Patternsmentioning
confidence: 82%
“…[10]), but one of the most controversial relates to the age of onset. Specifically, some research has suggested that adult-onset offending is a common phenomenon among females [8,19,20,23,24,34,57,62] and that this population of offenders has distinct risk factors in contrast to early or adolescent initiators [49]. Yet, findings from other studies suggest that adult-onset offenders represent a relatively trivial number of offenders overall [17,42] or that there are no true adult onsetters but rather delayed adolescent initiators (Sohoni, Paternoster, McGloin, and Bachman 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is also well-known that drug use is a key element in the socalled "Street Woman scenario" 3 (Daly, 1992) which in the literature is seen as a central pathway of female law breaking (e.g. Simpson et al, 2008).…”
Section: The Importance Of Drug Abusementioning
confidence: 99%
“…Plusieurs études avaient déjà souligné la dépendance de codélinquantes sexuelles à l'égard de leur conjoint (Tsopelas, Spyridoula et Athanasios 2011 ;Wijkman et al, 2010). La relation avec un individu antisocial est d'ailleurs liée à une délinquance exacerbée chez les femmes (Benda, 2005 ;Griffin et Armstrong, 2003 ;Simpson, Yahner, et Dugan, 2008). Étant incapables d'être seules, ces femmes feraient ce qu'elles peuvent pour conserver leur relation, qu'il s'agisse de tolérer certains comportements, notamment violents, ou d'en développer d'autres, comme des pratiques sexuelles douteuses.…”
Section: Relations Avec Le Codélinquantunclassified